History as passion and commitment. Interview with Alicia Alted Vigil - Ossenbach Sauter, Gabriela (Historia y Memoria de la Educación, 2019)
Interview with Alicia Alted Vigil, Professor of Contemporary History at the Universidad Nacional de Educación a Distancia (UNED) in Madrid, a specialist in the study of the Spanish Republican exile of 1939. The interview addresses his career since she worked in the 1980s in the cataloging of the archives of the republican government in exile, as well as her specialization in historical research with oral testimonies. Her research on the consequences of exile and civil war for children stands out especially.